2014
DOI: 10.3390/s140712285
|View full text |Cite
|
Sign up to set email alerts
|

Clustering-Based Ensemble Learning for Activity Recognition in Smart Homes

Abstract: Application of sensor-based technology within activity monitoring systems is becoming a popular technique within the smart environment paradigm. Nevertheless, the use of such an approach generates complex constructs of data, which subsequently requires the use of intricate activity recognition techniques to automatically infer the underlying activity. This paper explores a cluster-based ensemble method as a new solution for the purposes of activity recognition within smart environments. With this approach acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…Meanwhile, activity modelling is merely a representation of computational activity models in a computer interpretable format [17]. Data processing usually involves data segmentation and feature extraction while pattern recognition builds activity models based on generated smart home data [18]. Generally speaking, there are three main approaches used in the activity recognition, known as data-driven, knowledge-driven and hybrid approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, activity modelling is merely a representation of computational activity models in a computer interpretable format [17]. Data processing usually involves data segmentation and feature extraction while pattern recognition builds activity models based on generated smart home data [18]. Generally speaking, there are three main approaches used in the activity recognition, known as data-driven, knowledge-driven and hybrid approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Analyzing the scientific articles summarized in Table S7, presented in the Supplementary Materials file, it can be observed that 40% of them analyze smart buildings in general, while the remaining 60% take smart homes into consideration. The authors of these scientific articles make use of different types of sensors in their analyses, including smartphone sensors [16,20]; accelerometers providing inertial information of human activity [16]; Light-Emitting Diode (LED) luminaires used as light sensors [3]; and sensors associated with different objects [85,86]. In all of the papers selected and summarized in Table S7, the reason for using the Ensemble Methods integrated with the sensor devices in smart buildings was the recognition of human activity.…”
Section: Regressionmentioning
confidence: 99%
“…In all of the papers selected and summarized in Table S7, the reason for using the Ensemble Methods integrated with the sensor devices in smart buildings was the recognition of human activity. The performance metrics chosen by the authors of the scientific papers that use Ensemble Methods integrated with sensor devices in smart buildings include Accuracy [3,16,20,86]; Recall [16,85,86]; Precision and F-measure [85,86]; Mean Squared Error (MSE) [3]; and Confusion Matrix presenting a number of true Positives, True Negatives, False Positives and False Negatives [85].…”
Section: Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques have been proposed in literature for smart homes [187]. Beside, vision-based techniques, a number of sensor-based techniques have also been presented in the literature [188]. In [189], a genetic programming-based classifier was proposed for activity recognition in a smart home environment.…”
Section: Ambient Assisted Livingmentioning
confidence: 99%